Performance evaluation of the submerged abrasive water jet turning process for improving machinability of castamide - Basher Ibrahim, Salem A.; Seyma Korkmaz; Huseyin Cetin, M.; Fuat Kartal (Elsevier BV, 2020)
In this study, the submerged abrasive water jet turning (AWJT) system was used for improving machinability of castamide material and process parameters have been investigated comprehensively. Optimum parameters were determined as to minimize the surface roughness and maximize the material removal rate in the submerged turning process of castamide. 3-level traverse speed (TS), abrasive flow rate (AFR) and spindle speed (SS) were taken as the input parameters, and the experimental design was made as a full factorial design. The effect ratios of the input parameters were analyzed statistically by ANOVA and graphical methods, and their interactions were examined by 3D surface images. Optimum test condition was determined by TOPSIS and VIKOR methods. Experimental results were compared with conventional abrasive water jet process. In addition, regression equations were obtained for the explanation of the experimental results mathematically to show the relationships between the variables. According to the experimental results, submerged AWJT increased the surface roughness of castamide material by 15% compared to conventional AWJT and decreased the metal removal rate by 5.22%. ANOVA results showed that the traverse speed is the most effective parameter on the machinability of castamide. Traverse speed was found to be 83.11% effective on surface roughness and 85.56% on material removal rate. According to TOPSIS and VIKOR optimization results, 40 mm/min TS, 310 g /min AFR and 300 rpm SS values were determined as the optimum test conditions.
Keywords: Submerged turning; Castamide; TA1-2040; Abrasive water jet; TOPSIS; Engineering (General). Civil engineering (General); VIKOR